Earthquake Source Asymmetry, Structural Media and Rotation Effects - Teisseyre, Roman; Majewski, Eugeniusz; Takeo, Minoru; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This is the first book on rotational effects in earthquakes, a revolutionary concept in seismology. Existing models do no yet explain the significant rotational and twisting motions that occur during an earthquake and cause the failure of structures. This breakthrough monograph thoroughly investigates rotational waves, basing considerations on modern observations of strong rotational ground motions and detection of seismic rotational waves. To describe the propagation of such waves the authors consider structured elastic media that allow for rotational motions and rotational deformations of the ground, sometimes stronger than translational deformations. The rotation and twist effects are investigated and described and their consequences for designing tall buildings and other important structures are presented. The book will change the way the world views earthquakes and will interest scientists and researchers in the fields of Geophysics, Geology and Civil Engineering.
Macroseismic Rotation Effects and Micromotions -- Development of Earthquake Rotational Effect Study -- Sources of Rotation and Twist Motions -- Some Examples of Rotation Effects: the Tulbagh Earthquake, South Africa -- Theory of Continua and Fields of Defects -- Deviations from Symmetry and Elasticity: Asymmetric Continuum Mechanics -- Degenerated Asymmetric Continuum Theory -- Continuum with Rotation Nuclei and Defects: Dislocation and Disclination Densities -- Towards a Discrete Theory of Defects -- Fault Dynamics and Related Radiation -- A Review on Friction -- Soliton Physics -- Rotation Motions, Seismic Source Models, and Asymmetry of Fracture -- Rotational Motions Excited by Earthquakes -- Ground Rotational Motions Recorded in Near-Source Region of Earthquakes -- Fracture-Band Geometry and Rotation Energy Release -- Rotation Motions: Recording and Analysis -- Glacier Motion: Seismic Events and Rotation/Tilt Phenomena -- Rotational Energy and Angular Momentum of Earthquakes -- Bend-Rotation Wave as a Mechanism of Macroseismic Effects -- Solitary Waves in Crustal Faults and their Application to Earthquakes -- Seismic Rotation Waves: Spin and Twist Solitons -- Earth Rotation, Elasticity and Geodynamics: Earthquake Wave Rotary Model -- Effects Related to Medium Structures and Complexity of Wave Propagation -- Seismic Rotation Waves in the Continuum with Nonlinear Microstructure -- Tectonic Solitons Propagating Along the Fault -- Complexity of Rotation Soliton Propagation -- Micromorphic Continuum with Defects and Taylor-Bishop-Hill Theory for Polycrystals: Anisotropic Propagation of Seismic Waves and the Golebiewska Gauge -- Seismic Ray Theory for Structural Medium based on Kawaguchi and Finsler Geometry -- From Non-Local to Asymmetric Deformation Field -- Earthquake Hazard in the Valley of Mexico: Entropy, Structure, Complexity -- Seismic Rotational Motions: Recording Techniques and Data Analysis -- Note on the Historical Rotation Seismographs -- Ring Laser Gyroscopes as Rotation Sensors for Seismic Wave Studies -- Rotational Motions in Seismology: Theory, Observation, Simulation -- Absolute Rotation Measurement Based on the Sagnac Effect -- Design of Rotation Seismometer and Non-Linear Behaviour of Rotation Components of Earthquakes -- Rotation and Twist Motion Recording $1 (BCouple Pendulum and Rigid Seismometers System -- Equation of Pendulum Motion Including Rotations and its Implications to the Strong-Ground Motion -- Strong Motion Rotation Sensor -- High-Resolution Wide-Range Tiltmeter: Observations of Earth Free Oscillations Excited by the 26 December 2004 Sumatra -Andaman Earthquake -- Fiber Optic Sensors for Seismic Monitoring -- Rotations and Engineering Seismology -- Deriving Seismic Surface Rotations for Engineering Purposes -- Effects of Torsional and Rocking Excitations on the Response of Structures.s
Keywords: Earth sciences; Geology; Geophysics; Civil engineering; Earth Sciences; Geophysics/Geodesy.; Geology; Civil Engineering; Electronic books